EFFICACY OF SOFOSBUVIR IN COMBINATION WITH DACLATASVIR FOR THE TREATMENT OF HEPATITIS C GENOTYPE 3A PATIENTS IN A TERTIARY CARE CENTER IN PAKISTAN - Sohail Hussain, MBBS, FCPS; Sm Qamrul Arfin, MBBS, FRCP; Imtiaz Begum, MBBS, MRCP; Syed Ali Raza, MBBS, FCPS; Tauseef Ahmed, MBBS, FCPS; Jamil Muqtadir, MBBS, FCPS (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Patients with recurring illnesses of the hepatitis C virus frequently develop chronic liver disease, which causes tissue destruction ranging from cirrhosis to hepatocellular carcinoma (HCC). Hepatic-linked deceases are a result of this, both locally and globally. The efficacy of Sofosbuvir (SOF) and Daclatasvir (DCV) for treating individuals per enduring hepatitis C virus genotype 3a infection in either treatment-experienced or treatment-naive patients was examined in the study that was described below. At the Ziauddin Hospital North campus, a retrospective cohort research was carried out over 24 months, from January 2016 to December 2018. Regardless of the history of liver cirrhosis or behavior, patients with Genotype 3a HCV were treated for 12 weeks with Daclatasvir and Sofosbuvir.. Real-time PCR was cast-off to estimate the Sustained Virological Response (SVR12) 12 weeks following therapy. To do the statistical analysis, using SPSS version 20.0. In the study, there were 119 patients total, of which 79 (41.36%) were male, and 112 (58.63%) were girlish. The patient’s normal age stood 43.72 13.05. One hundred eighty-two patients (95.28%) had SVR12. Forty patients reported minimal side effects (18.32%). In conclusion, SOF with DCV is an excellent regimen for the genotype 3a virus and highly successful treatment for chronic HCV.